Soil Organic Carbondistribution, Mitigation and Management Practices - Banday, Muneesa; Gangoo, S. A.; Raja, Rameez; Pala, Nazir A.; Gatoo, Aasif A. (Indian Forester, 2019)
The 17 Sustainable Development Goals (SDGs) of the 2030 Agenda for sustainable development identified the need to restore degraded soils and improvement of soil health. Maintaining soil organic carbon storage at equilibrium or increasing content towards the optimal level for the local environment can contribute to achieving the SDGs. This can be achieved by unlocking the full ecosystem services potential of soils to enable not only the support, maintenance or improvement of soil fertility and productivity (necessary to achieve SDG 2 â€œZero Hungerâ€ and SDG 3 â€œGood Health and Well Beingâ€), but also to store and supply more clean water (SDG 3 and SDG 6 â€œClean Water and Sanitationâ€), maintain biodiversity (SDG 15 â€œLife on Landâ€), and increase ecosystem resilience in a changing climate (SDG 13 â€œClimate Actionâ€). Climate change has been since the 1980s. Soils are considered the biggest carbon reservoirs on earthat the centre of various international agreements on climate change. It is thus crucial to have a good knowledge of the current global SOC stock and its spatial distribution to inform various stakeholders (e.g. farmers, policy makers, land users) to make the best use of available land and provide the best opportunities to mitigate and adapt to climate change and to ensure sufficient food production and water supply. In the present review article we have tried to summarise the distribution and variability of SOC with respect to variation in soil, forest and other land use systems. The article identifies the best soil, forest and landuse systems for adoption in different regions for mitigation prospective.